2015
DOI: 10.1021/acs.jproteome.5b00391
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Serum Amyloid A for Infection Prediction in Aneurysmal Subarachnoid Hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is associated with high rates of mortality and morbidity. Nosocomial infections, such as pneumonia or urinary tract infections, are among the main causes of worsening outcomes and death. The aim of this study was to discover a biomarker to predict infection in aSAH patients. For this purpose, the plasma of infected and noninfected patients was compared using quantitative mass spectrometry. The most interesting differentially expressed proteins were selected for validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…In children with a variety of viral infections, SAA concentrations increased during the acute phase of infection [38]. In a small number of aSAH patients it has also been already proposed as an infection marker [12]. In agreement with this, in the present study we have found that, at admission, SAA concentrations in patients who develop an infection were significantly higher than those who did not.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In children with a variety of viral infections, SAA concentrations increased during the acute phase of infection [38]. In a small number of aSAH patients it has also been already proposed as an infection marker [12]. In agreement with this, in the present study we have found that, at admission, SAA concentrations in patients who develop an infection were significantly higher than those who did not.…”
Section: Discussionsupporting
confidence: 90%
“…We therefore combined aSAH clinical parameters with known blood diagnostic biomarkers of infection (SAA, CRP, NP, and WBC) in order to find the most effective combination to predict the infection. The combination of SAA, WBC, WFNS, and age showed 100% SP (95% CI, 100-100) and 64.3% SE (95% CI, 50-78.6); interestingly all four parameters included in this panel had already been described individually as markers of infection [12,29,31,32].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…SAA1/2 has already been described as a potential marker of inflammation and infection in several pathological conditions, including stroke and subarachnoid hemorrhage, [35]. In a case-controlled study involving 54 patients, levels of acute-phase proteins were significantly higher in stroke patients who developed an infection during the month preceding a cerebrovascular event than in those who did not develop one.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blood biomarker levels should be linked not just with general measures of prognosis such as disability or death, but with specific causes of worsening that culminate in poor outcome. Several studies have focused on biomarkers of stroke-associated infections such as IL-6, the Th1/Th2 profile, copeptin, procalcitonin or the recently described serum amyloid A 31. However, the accuracy, sensitivity and specificity of all these biomarkers are still not adequate for clinical use.…”
Section: Biological Datamentioning
confidence: 99%